Investigation of NH3 adsorption on 2D CuS nanostructures and sensing characteristics - Sahin, Ayse Nur; Altindal, Ahmet; Ozdemir, Zeynep Guven (SPRINGER, 2025)
CuS nanostructures have gained considerable attention for vapor sensing applications, owing to their distinctive optical, electrical, and adsorption characteristics. This study explores varied NH3 concentration (50-350 ppm) effects on the vapor sensing performance of 2D CuS sensors. The covellite-phase 2D CuS nanostructures were synthesized via the hydrothermal method and characterized by XRD, FE-SEM, UV-Vis, and FTIR measurements. NH3 adsorption kinetics were analyzed using pseudo-first order and Elovich models to elucidate the underlying mechanisms. The sensors exhibited strong response and rapid recovery at varied NH3 concentrations, demonstrating their high responses. Kinetic modeling was analyzed at 100, 200, and 350 ppm NH3 concentration and revealed a multilayer adsorption mechanism dominating at these concentrations for NH3. The sensor showed a maximum response of 79.16 at 200 ppm NH3 with response and recovery times of 434 s and 210 s, respectively at room temperature. FTIR and BET analyses further demonstrated NH3-induced surface restructuring and micropore activation, supporting a multilayer chemisorption-based sensing mechanism. Unlike limited reports that primarily attribute CuxS-based sensing to simple surface redox interactions, this work provides experimental evidence that multilayer chemisorption governed by heterogeneous surface sites is the dominant mechanism at high NH3 levels. Ultimately, this study provides an understanding of the adsorption behavior of NH3 on CuS nanostructures, demonstrating that multilayer chemisorption governed by heterogeneous surface sites dominates at higher concentrations. These findings highlight the fundamental sensing mechanism and provide a framework for optimizing CuS-based nanostructures to achieve enhanced sensitivity and long-term stability in next-generation NH3 sensors.
Keywords: COPPER SULFIDE; ELECTRICAL-PROPERTIES; COVELLITE CUS; GAS SENSORS; FILMS; NANOPARTICLES; ELECTRODE; GROWTH; Engineering; Materials Science; Physics